The Antioxidant Stability of Keluwak Powder (Pangium edule Reinw.) during Drying and Cooking - Estiasih, Teti; Sofia, Eva (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
Keluwak (Pangium edule Reinw.) is one of the Indonesian traditional spices that has spesific colour, taste, and flavour. Keluwak seeds contain antioxidant such as tocopherol, tocotrienol, and phenolic compounds. The utilization of keluwak traditionally has limitation due to short shelf life, time consuming preparation, and voluminous. Preparation of keluwak in the powder form can resolve these problems. However, the functional properties of keluwak as the source of antioxidant should be considered. The objectives of this research were to study the antioxidant stability during drying at keluwak powder preparation and the stability of antioxidant of keluwak powder during cooking. At keluwak powder preparation, two factors were elucidated i.e. drying method (foam mat drying and non foam mat drying) and maltodextrin concentration (10, 20, and 30% w/w). Completely Randomized Block Design that arranged factorially was used at keluwak powder preparation. The best treatment of keluwak powder preparation was used for the antioxidant stability assessment during cooking. The antioxidant stability of keluwak powder assessed during cooking were method of cooking, i.e. stirring (0, 3, 6, 9 minutes) and boiling (0, 30, 60, 90 minutes). Each treatments replicated three times. Descriptive method was used in this step. The results showed that method of drying (foam mat and non foam mat) significantly affected phenolic content, tocopherol concentration, antioxidant activity, and yield of keluwak powder. The best keluwak powder produced (physico-chemical properties) was obtained from the combination of non foam-mat drying and 10% of maltodextrin concentration. It had 19.19 ppm of total phenol, 252.2 ppm of tocopherol, 76.67% of antioxidant activity, and 36.65% of yield. Stability of antioxidant activity keluwak powder decreased as time of heating (stiring and boiling) increased proportionally.Keywords: keluwak, antioxidant activity, foam mat drying, antioxidant stability